Scanning electron microscopy-energy dispersive X-ray spectrometry (SEM-EDX) and aerosol time-of-flight mass spectrometry (ATOFMS) single particle analysis of metallurgy plant emissions. (March 2016) - Arndt, J.; Deboudt, K.; Anderson, A.; Blondel, A.; Eliet, S.; Flament, P.; Fourmentin, M.; Healy, R.M.; Savary, V.; Setyan, A.; Wenger, J.C.
Abstract: The chemical composition of single particles deposited on industrial filters located in three different chimneys of an iron-manganese (Fe–Mn) alloy manufacturing plant have been compared using aerosol time-of-flight mass spectrometry (ATOFMS) and scanning electron microscopy–energy dispersive X-ray spectrometry (SEM-EDX). Very similar types of particles were observed using both analytical techniques. Calcium-containing particles dominated in the firing area of the sintering unit, Mn and/or Al-bearing particles were observed at the cooling area of the sintering unit, while Mn-containing particles were dominant at the smelting unit. SEM-EDX analysis of particles collected downstream of the industrial filters showed that the composition of the particles emitted from the chimneys is very similar to those collected on the filters. ATOFMS analysis of ore samples was also performed to identify particulate emissions that could be generated by wind erosion and manual activities. Specific particle types have been identified for each emission source (chimneys and ore piles) and can be used as tracers for source apportionment of ambient PM measured in the vicinity of the industrial site. Highlights: Similar composition for emitted particles as those collected on the chimney filters. Emitted particles dominated by Ca-, Mn and/or Al-containing particles. Identification of specific particle types emitted by the different process units. Abstract : The particles emitted by metallurgy activities are fully described by ATOFMS and SEM-EDX, enabling the identification of specific particle types from the different units of the process.